Formulation and Physical Stability Test Peel Off Mask from Kokang Leaf Extract ( Lepisanthes amoena (Haask) Leenh) as an Antioxidant - Jati Pratiwi; Ika Ayu Mentari (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Free radicals are substances that can damage skin cell membranes and damage skin cells resulting in melanogenesis which is the main defense of the skin. So that antioxidants are needed as an antidote to free radicals that can inhibit or neutralize the bad effects of free radicals and are formulated in the form of peel-off masks to remove dirt and dead skin cells. Kokang leaves (Lepisanthes amoena (Haask) Leenh) is a plant rich in antioxidants originating from East Kalimantan which contains alkaloids, flavonoids, saponins and tannins. This study aims to determine the characteristics and physical stability as well as determine the antioxidant activity of peel off mask preparations of kokang leaf extract (Lepisanthes amoena (Haask) Leenh), experimentally using the DPPH method with a UV-Vis spectrophotometer. The results and conclusions obtained were that kokang leaf extract (Lepisanthes amoena (Haask) Leenh) peel off mask preparations 1 (0%), 2 (1%), 3 (2.5) and 4 (5%) had physical characteristics and stability good tests (meet standard requirements) including organoleptic tests, pH, homogeneity, spreadability, adhesion, drying time and viscosity. Testing the antioxidant activity using a concentration of 5%. Kokang leaf extract contains strong antioxidant activity with a value of 59,707 ppm, while kokang leaf extract peel off mask contains medium category antioxidant activity with an IC50 value of 102,945 ppm.